Analisis Kepuasan Pengguna Aplikasi E-Learning Ruangguru Di Kalangan Pelajar SMA Menggunakan Model EUCS - Ananda, Feroz Fairus; Husin, Arif Ismail; Rakhmah, Syifa Nur (INFORMATICS FOR EDUCATORS AND PROFESSIONAL : Journal of Informatics; Vol 10 No 2 (2025): INFORMATICS FOR EDUCATORS AND PROFESSIONAL : JOURNAL OF INFORMATICS (Desember 2025)DO - 10.51211/itbi.v10i2.3715, 2025)
This study aims to analyze the level of satisfaction of Ruangguru e-learning application users among high school students. This study uses the End User Computing Satisfaction (EUCS) model, which consists of five main aspects, namely content, accuracy of information, format, ease of use, and timeliness. The research was conducted quantitatively by distributing questionnaires to 397 high school students who use the Ruangguru application. The data obtained was then analyzed using various tests such as validity, reliability, t-test, F-test, and coefficient of determination tests with the help of SPSS version 30. The results showed that all five variables in the EUCS model had a significant effect on the level of satisfaction of Ruangguru app users. This was evident from the calculated F value being greater than the F table value and the significance value being less than 0.05. In addition, the determination test results showed that these variables collectively contributed significantly to user satisfaction with the app. Thus, it can be concluded that the Ruangguru application is able to meet the expectations of high school students in terms of content, accuracy of information, ease of use, presentation format, and speed of service.